An Integrated Conceptual Framework for Proactive Improvement of Safety Culture - Ali, Shahid; Shariff, Azmi Mohd (International Review of Management and Marketing, 2016)
Over the past three decades safety culture studies have bridged many gaps by developing specific existing culture models to workplace environment. But there is still no consensus over the core factors of safety culture, methods and improvement strategies. This conceptual work proposes a different approach by integrating the present general and workplace models to develop a new integrated framework of proactive assessment model for safety culture. In doing so, an summary of the current general and workplace literatures will be provided as well as their homogeneities and differences emphasized. This conceptual framework can be the basis for further research in order to provide a comprehensive picture of the safety culture assessment process. Lastly, implications for specific interventions to develop targeted Safety Culture assessment practices and work towards achieving sustainable safety culture will be discussed. Keywords: Safety Culture, Proactive, Reactive, Benchmarking JEL Classification: M1